Contract workers at Higher Education Institutions within a framework of motivational leadership - Jooste, Karien; Arunachallam, Sathasivan; Essa, Ilhaam; Rashe, Vuyiswa (South African Journal of Higher Education, 2016)
Most literature sources are based on negative assumptions about contract workers and career success. Despite the growing number of contract workers at higher education institutions, and the changes it elicits in the work place, there has been little theoretical work conducted about a positive perspective of contract workers in relation to achieving organisational or personal goals. A review of the topic about contract workers has been undertaken from the perspective of motivational leadership, with incorporation of the theoretical perspectives of path goal and great man’s theories. Keywords Contract workers, higher education, nursing, university, motivational leadership